Kontribusi Balai Latihan Kerja (BLK) dalam Meningkatkan Keterampilan Kerja, Motivasi Kerja dan Minat Berwirausaha pada Generasi Muda - Fathuddin Abdi (Indonesian Journal of Islamic Economics and Business, 2019)
This study aims to determine the contribution of the Jambi Province Job Training Center called (BLK) and its role in Empowering Work Skills, Increasing Work Motivation and Entrepreneurial Interest in the Young Generation. The data were collected by observation, interviews and documentation. This study uses the descriptive qualitative approach with the sampling method using snowball sampling. The data analysed by interactive analysis technique, namely by reducing data, presenting data, and imparting conclusions. The results of this study all participants which is taking part in training at the Work Training Center of Jambi Province, especially in this study, namely the Apparel Garment Program Assistant major Clothing makers and the Automotive program, majoring in Motorbike Junior Mechanics, certainly have a very important role for participants in finding job vacancies, and even gain skills training with the belief that they can open their own business by provision of skills possessed.